Correlations between basic geotechnical properties of peat soil in new study area in Sarawak - Ahmad Hafidzur Rahman, Ahmad Nidhom (Universiti Malaysia Sarawak, UNIMAS, 2009)
In engineering terms, peat is one of examples of soft soils and it poses serious problems in construction due to instability and long term consolidation settlement even when subjected to a moderate load. Engineers are facing problems in understanding the properties of peat and due to demands they have to find suitable ways to construct structures on peats. Therefore it is essential to have deep understanding of peat properties so that a suitable technique for foundation will be selected. Sarawak has the largest peat area in Malaysia with 16,500 km2 that makes up 13% of the state. The most types of peat in Sarawak are fibrous and amorphous with high organic content. This study is to develop correlation of basic properties of peat in new study area in Sarawak and to compare the correlation made with correlations that already made from previous findings. It was found that the peat soil in Sarawak is not similar to that in West Coast Peninsula Malaysia. The result indicates that the dry density correlates well with natural moisture content. Furthermore, it was found that the liquid limit and organic content decreasing with increasing moisture content but the findings from West Coast Peninsula Malaysia shows contradiction of it.